Synthesis, Characterization and Thermal Studies of a New Imine-oxime Ligand and its Cu2+, Ni2+, Co3+ and Zn2+ Complexes - Kaya, Yunus; Irez, Gazi; Mutlu, Hasene (Asian Journal of Chemistry, 2010)
(2E)-3-Aza-1-(hydroxyimino)-2,4-diphenylpent-2-ene (HL) was synthesized by the reaction of isonitrosoacetophenone with 1-phenyl-1-aminoethane in 1:1 molar ratio. The ligand was characterized by using IR, 1H NMR, 13C NMR, UV-vis spectra, elemental analysis, thermal analysis and mass spectroscopy. Ni(II), Cu(II), Co(III) and Zn(II) complexes of this ligand were synthesized and their structures were identified using AAS, IR, electronic spectra, thermal analysis, mass spectroscopy, elemental analyses, conductance and magnetic moment measurements. In the process of obtaining Co(III) complex, when the cobalt(II) chloride solution was added into the alcoholic solution of the ligand gave orange colored complex by air oxidation and this complex was seen polymeric and diamagnetic in nature.